Barriers of learning process among faculty of Office Management and Technology (FPTP) students in UiTM Perak / Siti Nor Sofia Ahmad, Rashida Dan @ Zain and Rosazila Rapelis - Ahmad, Siti Nor Sofia; Dan @ Zain, Rashida; Rapelis, Rosazila (2010)
The purpose of the study was to investigate the barriers of learning process among students of the Faculty of Office Management and Technology (FPTP) in UiTM Perak. Questionnaires were distributed randomly selected among of one thousand two hundred and eighty six students in both diploma and degree programs in the Faculty of Office Management and Technology, UiTM Perak. The survey measured demographic proiles, factors that affect the learning process and respondents' perception on overcoming barriers to the learning process. The results showed that lack of focus in the classroom was the biggest barrier in the learning process. The results showed the factors that the respondents perceived to be somewhat a big barrier were' lack of focus in cla s , stre s due to 'overcrowded clas es' and 'too much assignments/test/quizzes', 'financial problem', 'students are too embarrassed to ask questions', 'lack of facilities provided in classes' and 'lack of computer facilities'. The results also showed that respondents perceived to be omewhat a small barrier to the learning process were 'stress due to personal problems', 'age gap between students and lecturers', 'relationship with lecturers', different gender between student and lecturer', language problem faced by student', 'an ineffective lecturer' and 'lack of reading materials'.The results showed that more than half of the respondents thought that lectures are the right people that students should talk about the barriers of the learning process faced by the students; student's attitudes affect them academically, personal problems interfere with student's focus in the class; time management is important in the learning process; the effectiveness of deli very in class benefits students; I always ask questions in class; participation in class is very important for students' understanding and the effectiveness of learning process is very impo1tant to student's academic achievement.